Predictors of Obesity among Type 2 Diabetes Mellitus Patients Attending a Tertiary Care Center of Province 1, Nepal - Roy, Pratap Kumar; Baral, Dharanidhar; Gautam, Arjun; Subedi, Sarita (Journal of Nobel Medical College, 2022)
Background: Obesity and Diabetes Mellitus type 2 have a known association. Yet, the socio-demographic predictors of obesity in special populations like ours (Asian) who have DM remain unclear. The purpose of this study was to determine the socio-demographic predictors of obesity among newly diagnosed Diabetes Mellitus in adults. Materials and Methods: This was a descriptive cross-sectional study conducted in endocrine OPD of Nobel medical college. Total 124 subjects were enrolled who were newly diagnosed Diabetes Mellitus over a period of 1 year. Detailed history was taken for demographic and clinical variables. Height, weight, waist circumference and blood pressure were measured. Besides, Body Mass Index, the dependent variable, was calculated. Subjects were considered to have diabetes based on their fasting and postprandial blood sugar level for the first time. Results: The prevalence of obesity among the study population was 39.5%, overweight was 45.2%. Predictors for this study for obesity were found as abnormal blood pressure and hospital visit after symptoms development. Conclusion: Obesity is a important risk factor for Diabetes Mellitus and higher prevalence of obesity among type 2 diabetes was observed. Predictors for this study for obesity were found as abnormal blood pressure and hospital visit after symptoms development